Ask a New Question
Search
Questions and answers by
Steve - Ouch
Answers (7)
Oh, yeah -- that's what I meant Funny how things like that slip past... I must have been thinking of the (-1)^2 and being careful about the sign, and not the value. Thanks for the catch.
Oops. Did you catch my typo? Look again...
I made a typo. Maybe Henry's solution will be better. Either approach will work if done carefully.
rats. Way to watch.
ahem ... (3ab^2)/(4ab) * (3a^2b)/(4a) = 3b/4 * 3ab/4 = 9ab^2/16
I see a typo. Let's proceed from 4(2x-3)(x-2) - (2x+3)(x-2) = 4(2x+3)(2x-3) 6x^2-27x+30 = 16x^2-36 10x^2+27x-66 = 0 x = (-27±√3369)/20 Not much better.
Way to watch, scott. I saw a fraction and assumed the worst.